Constitutional Court Rulings on Electoral Thresholds in Indonesia: Putusan Mahkamah Konstitusi tentang Ambang Batas Pemilihan di Indonesia - Muhammad Mirza Faldinan Azharil; Rifqi Ridlo Phahlevy (Academia Open, 2025)
General Background: Electoral thresholds constitute a central feature of Indonesia’s electoral system, shaping candidate nomination and parliamentary representation within a presidential democracy. Specific Background: Since the post-reform era, regulations on presidential and parliamentary thresholds have repeatedly been reviewed by the Mahkamah Konstitusi, generating numerous rulings that define their constitutional status and legal interpretation. Knowledge Gap: Prior discussions tend to focus either on doctrinal justification or political consequences, leaving limited synthesis of how judicial decisions collectively construct the notion of open legal policy in electoral governance. Aims: This study analyzes the trajectory of Constitutional Court rulings on presidential and electoral thresholds from 2004 to 2024 to identify patterns of reasoning, consistency, and constitutional framing. Results: Examination of 24 decisions demonstrates that the Court has consistently upheld threshold provisions as constitutionally permissible under legislative discretion, despite recurring claims that they restrict political participation and candidate diversity. Novelty: The research offers an integrated juridical assessment that maps long-term judicial continuity while situating thresholds within debates on participatory democracy and constitutional interpretation. Implications: These findings clarify the legal foundations of threshold regulations and provide a reference for policymakers, scholars, and reform advocates assessing the balance between electoral stability and inclusive democratic competition in Indonesia. Highlights: Judicial reasoning repeatedly affirms legislative discretion in setting nomination requirements. Legal challenges frequently fail due to issues of standing rather than substantive review. Ongoing controversy reflects tension between stability considerations and broader candidate access. Keywords:Constitutional Court; Electoral Threshold; Presidential Threshold; Open Legal Policy; Participatory Democracy